Dual functions of pH-sensitive cation Zr-MOF for 5-Fu: large drug-loading capacity and high-sensitivity fluorescence detection. Issue 30 (14th July 2021) - Sun, Xi-Yu; Zhang, Hong-Jing; Zhao, Xiao-Yang; Sun, Qian; Wang, Yuan-Yuan; Gao, En-Qing
Abstract : N -methylation cationic metal-organic framework UiO-67-CDC-(CH3 )2, simulates as drug delivery system and visual colorimetric fluorescence sensor. Abstract : Nanomaterials, as carriers of small molecular drugs, have been a focal point in recent years. In this work, a carbazolyl functionalized metal–organic framework, UiO-67-CDC, was successfully synthesized employing the ligand 9 H -carbazole-2, 7-dicarboxylic acid (9 H -2, 7-CDC). Postsynthetic approaches targeted the cationization and replacement of the Lewis base carbazole site with two methyl groups, resulting in the positively charged skeleton, which has proven to be a promising carrier for the anticancer drug 5-fluorouracil (5-Fu). The prepared cationic framework UiO-67-CDC-(CH3 )2 showed moderately high surface area, hierarchical pore structures, and positive surface characteristics, which effectively and selectivity encapsulated the electron-rich 5-Fu molecules through electrostatic attraction, with a relatively high loading of up to 56.5% (wt%). The drug delivery in simulated blood environment (pH = 7.4) exhibited a more effective release, demonstrating a physiological pH-responsive sustained release. Significantly, the electron-deficient Zr-MOF itself, as a kind of high-sensitivity fluorescence detector, has a unique fluorescence "turn-on" effect with 5-Fu. These results pave the way towards designing surface-engineered MOF materials of interest in drug delivery and fluorescent sensing applications.